2014
DOI: 10.1002/adfm.201303384
|View full text |Cite
|
Sign up to set email alerts
|

Highly Intensified Surface Enhanced Raman Scattering by Using Monolayer Graphene as the Nanospacer of Metal Film–Metal Nanoparticle Coupling System

Abstract: It is widely accepted that surface enhanced Raman scattering (SERS) enhancement results from a combination of electromagnetic mechanisms (EM) and chemical mechanisms (CM). Recently, the nanoparticle-fi lm gap (NFG) system was studied due to its strong local enhancement fi eld. However, there are still some technical limitations in establishing effective and simple ways for reliable and precise control of sub-nanospacer. In addition, works on designing the nanospacer in NFG system for effi cient interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
140
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 65 publications
4
140
0
Order By: Relevance
“…While complex and laborious procedures are needed for coupling graphene to nanostructured surfaces, 7,8,17 GO coating can be simply obtained by physisorption of GO sheets in…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While complex and laborious procedures are needed for coupling graphene to nanostructured surfaces, 7,8,17 GO coating can be simply obtained by physisorption of GO sheets in…”
Section: ■ Introductionmentioning
confidence: 99%
“…While complex and laborious procedures are needed for coupling graphene to nanostructured surfaces, 7,8,17 GO coating can be simply obtained by physisorption of GO sheets in aqueous solution. 18−21 Beside obvious advantages of this approach, a detailed investigation on how the assembly of GO should be conducted to control adsorption geometry and optical properties at the interface is still lacking.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] In particular, the approach is extremely important for the chemically functionalized graphene samples because it allows to identify the functional groups on the graphene surface. [3] However, it is also known that graphene may strongly interact with the metals, and this interaction is also mirrored in the Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many groups focused on in-deep understanding of the effect inspecting various scenarios. [2,13] For example, Sun et al proposed that a large SERS enhancement is a joint effect of the charge transfer and electromagnetic coupling, which is closely correlated with the near-field plasmon coupling of Ag nanoparticles in contact with the graphene bilayer. [14] He et al studied the Raman signal enhancement using Au nanorods [15] and concluded that when the resonant wavelength of the Au nanorods matches well with excitation laser wavelength, the Raman enhancement factor is highest up to 1,000-fold.…”
Section: Introductionmentioning
confidence: 99%